Isolamento de fungos produtores de ácido γ-linolênico de solo da Estação Ecologica de Juréia-Itatins, SP - Ruegger, Marcelo José Silveira [UNESP]; Tauk-Tornisielo, Sâmia Maria [UNESP]; Pastore, Gláucia Maria (My University, 2002)
Fungi producing γ-linolenic acid (GLA) were isolated from soil of the Ecological Station of Juréia-Itatins, SP. This essential fatty acid has aroused great interest due to its increasing by applications in pharmaceutical industry. The GLA production by zygomycetous fungi is an alternative way of comparing seed extraction. Thirty-two zygomycetous strains of Mucorales were isolated, most of them belonging to Mucor genus. The GLA production was evaluated after 4 days of incubation at 25°C on a rotary shaker at 150 rpm in medium containing 2% glucose, and 1% yeast extract, following new medium addition (20%) and incubation for an additional period of 3 days at 12°C, without agitation. The GLA production varied according to the microorganism and the strain.
Fungi producers of γ-linolenic acid isolated from the soil of the Ecologic Station of Juréia-Itatins, SP
Keywords: γ-linolenic acid; Essential fatty acid; Fungi; Zygomycetes; gamma linolenic acid; natural product; addition reaction; Brazil; culture medium; extraction; fatty acid synthesis; fungus; incubation time; isolation procedure; Mucorales; nonhuman; plant seed; product recovery; soil analysis; strain identification; temperature measurement